PERAN PENGETAHUAN PERPAJAKAN DALAM MENINGKATKAN KEPATUHAN PAJAK UMKM: SEBUAH SYSTEMATIC LITERATURE REVIEW - Nasihah, Arifatun; Kahfi Fikrianoor (Jurnal Akuntansi, 2026)
This study aims to analyze the role of tax planning in improving tax compliance among Micro, Small, and Medium Enterprises (MSMEs) through a Systematic Literature Review (SLR) approach. MSMEs are a strategic sector that contributes significantly to the national economy; however, their level of tax compliance remains relatively low due to various challenges, including limited tax literacy, administrative complexity, and the perception that taxes impose a burden on business operations. This study employs a Systematic Literature Review method involving the identification, selection, quality assessment, and synthesis of relevant empirical and theoretical literature from national and international journals. The findings indicate that effective tax planning, conducted in accordance with prevailing tax regulations, can assist MSMEs in managing their tax obligations more efficiently, reducing administrative errors, and improving compliance in tax reporting and payment. The effectiveness of tax planning is influenced by tax policies, tax regulations, and tax administration systems. In addition, factors such as tax rates, administrative sanctions, taxpayer perceptions, and tax morale also affect the level of tax compliance. The main challenges faced by MSMEs in implementing tax planning include bureaucratic complexity, limited tax knowledge, and inadequate access to tax education and assistance.